Childhood unintentional injuries: Supervision and first aid provided - Annabel Jonkheijm; Jenny Johanna Hendrijntje Zuidgeest; Monique van Dijk; Àrjan Bastiaan van As (Wolters Kluwer Medknow Publications, 2013)
Background : The aim of this study was to investigate the circumstances surrounding unintentional injuries of children and the appropriateness of the first aid provided by caregivers. Materials and Methods : This prospective study included children with aged range 0-12 years, who presented with an unintentional injury at the Trauma Unit of a hospital in Cape Town, South Africa, over a 3 month period. Caregivers were interviewed about the circumstances of the injury and the first aid provided. Experts classified the first aid as appropriate, appropriate but incomplete, or inappropriate. Results: A total of 313 children were included with a median age of 3.75 years. The most common causes of injury were falls (39.6%, n = 124), burns (23.9%, n = 75) and motor vehicle crashes (10.5%, n = 33). More than a quarter of the children (27.2%, n = 81) had been left under the supervision of another child below the age of 12. When the injury occurred, 7.1% (n = 22) of the children were unattended. First aid was provided in 43.1% (n = 134) of the cases. More than half of these interventions (53%, n = 72) were inappropriate or appropriate but incomplete. Conclusions: Especially young children are at risk for unintentional injuries. Lack of appropriate supervision increases this risk. Prevention education of parents and children may help to protect children from injuries. First-aid training should also be more accessible to civilians as both the providing of as well as the quality of first-aid provided lacked in the majority of cases.